Bayesian methods in health economics: Bayesian principles 1 - O'Hagan, Anthony (Henry Stewart Talks, 2009)
Bayesian statistics, Frequentist statistics, Bayesian vs. frequentist approach, Prior distribution, Triplots, Posterior distribution, Statistical computational tools, Statistical inference, The nature of parameters, The use of prior information, The nature of probability
Reviewed at 2022/03/30